Global public awareness about atrial fibrillation. Issue 1 (25th October 2017) - Wendelboe, Aaron M.; Raskob, Gary E.; Angchaisuksiri, Pantep; Blanco, Alicia N.; Büller, Harry; Ddungu, Henry; Dvorak, Justin D.; Hunt, Beverley J.; Hylek, Elaine M.; Kakkar, Ajay; Konstantinides, Stavros V.; McCumber, Micah; et al.
Abstract: Essentials Early recognition of atrial fibrillation helps in stroke prevention. Survey in 10 countries to assess public awareness of atrial fibrillation. Overall global awareness of atrial fibrillation was 48%. Less than 46% of participants were aware atrial fibrillation leads to stroke. Background: Atrial fibrillation (AF) is an important cause of ischemic stroke that often remains undetected until stroke occurs. Awareness of the risk factors and symptoms is important so that AF can be diagnosed and thromboprophylaxis given. However, the extent of public awareness of AF is uncertain. We assessed public awareness of AF across six continents and compared it with that of other thrombotic and non‐thrombotic disorders. Methods: In collaboration with Ipsos‐Reid, we conducted an internet‐based, cross‐sectional survey between September and October of 2016 in 10 countries: Argentina, Australia, Canada, Germany, Japan, Thailand, the Netherlands, Uganda, United Kingdom, and United States. Participants were selected from survey panels in weighted, age‐stratified categories (40‐60, 61‐74, and ≥75 years). The survey included 11 questions about demographics and assessed awareness about AF, as well as that of other thrombotic and non‐thrombotic disorders. Proportions and 95% confidence intervals (CI) were calculated. Results: Of a total of 6312 respondents, overall awareness of AF was 48% (95% CI, 46‐50%), which was lower than awareness about other thrombotic and non‐thrombotic disorders except for deep vein thrombosis (awareness 43%, 95% CI, 41‐45%). Awareness about AF ranged from 25% to 69% across countries, while awareness of the risk factors for AF ranged from 8% to 52%, and awareness that AF leads to stroke ranged from 36% to 46%. Among those reporting awareness of AF, 82% correctly identified palpitations as an AF symptom. Conclusions: Global public awareness of AF is low. Improving awareness may empower patients to seek timelier stroke preventive care.